Effects of near-field earthquakes, connection types, and SSI on seismic performance of SMRF - Bakhshpoori, T.; Nezhad, A.R. Nazari (Structures (Oxford), 2024)
This study aims to validate the ASCE7–16 code, which investigates the effects of near-field earthquakes, Soil-Structure Interaction (SSI), and connection types on the seismic performance of the code-conforming Steel Special Moment-Resisting Frames (SMRFs). To this end, three structures with 4, 9, and 16 stories representing low, mid, and high-rise buildings are designed, respectively, according to the ASCE7–16 and AISC 360–16 codes. In order to evaluate the effect of connections’ type on the seismic performance, two prequalified connections, namely Welded Unreinforced Flange-welded Web (WUF-W) and Reduced Beam Section (RBS) are taken into account. Afterward, for the sake of seismic assessment, an internal frame is selected from each building model, in which, the Nonlinear Time-History Analysis (NTHA) is conducted using OpenSees software. Then, a set of far-field and three sets of near-field (with/without pulse-like records, including forward-directivity as well as fling-step) ground motions are selected, where each set consist of 12 earthquake records. The Inter-story Drift Ratio (IDR) is considered as a major indicator to assess the seismic performance of the structures. Based on the obtained results, subject to the pulse-like ground motion records, the IDR values exceed the allowable limits specified by ASCE 7–16, and additionally, it is found that the SSI effects change the height-wise distribution of the IDR, highlighting the need for revising the provisions of ASCE 7–16. Eventually, the seismic responses are investigated according to ASCE 41–17 and the performance limits of the structures are obtained accordingly. The results indicate that all structures manage to satisfy the acceptable performance limits.